the digitalization strategy of human resouces management to improve teacher performance: STRATEGI DIGITALISASI MANAJEMEN SDM UNTUK MENINGKATKAN KINERJA GURU - Iflaha, Nurul (widya balina, 2025)
Digitalization in human resource management in the education sector is a strategic step to increase the effectiveness and efficiency of teacher performance. This study aims to determine the HR management strategy by integrating digital to improve the performance of the HR in it, namely teacher. This research was conducted through a literature study by reviewing various relevant sources, such as articles, books, research reports and other references related to HR management in education, teacher performance and digitalization in education. A qualitative approach is used to examine and understand varius strategies that have been proposed by previous researchers. The results of study indicate that the digitalization strategy in HR management can be carried out by carrying out careful planning for the implementation of digitalization into HR management, implementing a digital HR management information system and training educators so that they have sufficient skills and understanding in utilizing digital technology. This research contributes to broadening the understanding of human resource management strategies to improve teacher performance amidst the development of digitalization in educational institutions. These findings can be used as a reference by policy makers and education practitioners in developing strategies to improve the quality ef education in the digital era.